1993
DOI: 10.1159/000263821
|View full text |Cite
|
Sign up to set email alerts
|

Age of Gestation (Size) at Embryonic Demise: Taiíoring Counseling for Lethal versus Potentially Viable Aneuploidy

Abstract: The incidence of chromosomal abnormalities in spontaneous abortions is much higher than commonly appreciated. Using postmortem chorionic villus sampling (as we have previously described), our much increased yield of results allows us to divide embryos into two groups based upon potential viability. Embryonic size at the time of demise correlated with viability, i.e., the more ‘viable’ the embryo for term survival. Even in the absence of chromosomal results, the size of the embryonic pole can be used to infer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…We found that in the CVS patient group, using a threshold of 3 mm, that over 50% of such cases were associated with chromosome abnormalities. We further found that when there was a fetal demise, that the more 'abnormal' the aneuploidy was, the earlier in gestation the fetus died [49,50]. For those that didn't die, the prevalence of first trimester intrauterine growth retardation was increased.…”
Section: Biochemical Screeningmentioning
confidence: 73%
“…We found that in the CVS patient group, using a threshold of 3 mm, that over 50% of such cases were associated with chromosome abnormalities. We further found that when there was a fetal demise, that the more 'abnormal' the aneuploidy was, the earlier in gestation the fetus died [49,50]. For those that didn't die, the prevalence of first trimester intrauterine growth retardation was increased.…”
Section: Biochemical Screeningmentioning
confidence: 73%
“…There is a differential effect of the chromosome anomaly involved on the length of gestation, with all cases affected by trisomy 16, 70-80% of pregnancies affected by trisomies 13 and 18, and about 30% of trisomy 21 fetuses being aborted spontaneously. Moreover, the more significant the chromosome aberration, the higher the likelihood that pregnancy will be lost at an earlier stage in gestation [9]. Thus, it would be expected that evaluation of aneuploidy in specimens obtained for prenatal diagnosis would be more accurate than in neonates, the latter being skewed by differing rates of spontaneous pregnancy loss.…”
Section: Discussionmentioning
confidence: 99%